(untitled) (World Bulletin of Education and Learning, 2025)
This article analyzes the specific features of the "tazkira genre", which occupies a special place in the classical literary heritage of the East. It highlights how the author’s personal views, aesthetic taste and philosophical worldview are combined with historical realities. The works of Davlatshah Samarkandiy “Tazkirat ush-shuaro”, Alisher Navoiy’s “Majolis un-nafois”, “Nasoyim ul muhabbat” and Abdurakhmon Jamiy’s “Bahoristan” are used as examples to show the subjective assessment in tazkiras, the interrelation of the literary environment of the period and historical reality.